2010
DOI: 10.3109/15622975.2010.507784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic stress on apoptosis and the expression of TRPM2 in human olfactory neuroepithelial-derived progenitors

Abstract: Our findings suggest that the elevation of [Na(+)](in) and [Ca(2+)](in) induced ONP apoptosis and altered the expression of TRPM2. Lithium pretreatment attenuated the apoptosis induced by ionic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…Cellular effects of lithium, a first-line bipolar disorder treatment, have also been explored in ON-derived cells, revealing amelioration by lithium of ionic stress-induced apoptosis and TRPM2 overexpression. 141 In major depressive disorder, there is evidence that ON-derived cells display decreased nuclear translocation of the glucocortocoid receptor, GR, in response to glucocorticoids relative to controls. 142 This diminished receptor translocation was accompanied by greater cytoplasmic association of GR with the immunophillin FKBP51.…”
Section: The Use Of Om-derived Cells In Psychiatry and Neuroscience Rmentioning
confidence: 99%
“…Cellular effects of lithium, a first-line bipolar disorder treatment, have also been explored in ON-derived cells, revealing amelioration by lithium of ionic stress-induced apoptosis and TRPM2 overexpression. 141 In major depressive disorder, there is evidence that ON-derived cells display decreased nuclear translocation of the glucocortocoid receptor, GR, in response to glucocorticoids relative to controls. 142 This diminished receptor translocation was accompanied by greater cytoplasmic association of GR with the immunophillin FKBP51.…”
Section: The Use Of Om-derived Cells In Psychiatry and Neuroscience Rmentioning
confidence: 99%
“…Utilize neuronal cells obtained from patients and controls (e.g., induced pluripotent cells [104] or olfactory neuroepithelial cells [105]) in order to determine the differential effect (if any) in the response of neural tissue derived from patients with BD and non-psychiatric controls. Early exploratory evidence from immortalized lymphoblasts [106], induced pluripotent cells, and olfactory neuroepithelial progenitors [107][108][109][110][111], suggests that such differences exist.…”
mentioning
confidence: 99%
“…Previous studies have shown that MNS inhibits the cell proliferation as a consequence of arresting the cell-cycle progression, leading to apoptotic cell death in various cells (Park et al, 2002a(Park et al, , 2002b(Park et al, , 2003a(Park et al, , 2003b. Furthermore, MNS has recently been shown to cause oxidative damage to the cells, resulting in the apoptotic cell death in olfactory neuroepithelial-derived progenitors and prostate cancer cells (Gao et al, 2010;Ketola et al, 2010). In contrast, the findings presented in this paper suggest that PTX can cause the cytotoxic action through a different mechanism from that of MNS, and provide evidence for supporting the nonoxidative and necrotic action of PTX on PC12 cells.…”
Section: Discussionmentioning
confidence: 99%